catch +transformers

catchError :: (Monad m, Error e) => ErrorT e m a -> (e -> ErrorT e m a) -> ErrorT e m a
transformers Control.Monad.Trans.Error
Handle an error. *  h (lift m) = lift *  h (throwError e) = h
liftCatch :: (m (Maybe a) -> (e -> m (Maybe a)) -> m (Maybe a)) -> MaybeT m a -> (e -> MaybeT m a) -> MaybeT m a
transformers Control.Monad.Trans.Maybe
Lift a catchError operation to the new monad.
liftCatch :: (m (a, s) -> (e -> m (a, s)) -> m (a, s)) -> StateT s m a -> (e -> StateT s m a) -> StateT s m a
transformers Control.Monad.Trans.State.Lazy, transformers Control.Monad.Trans.State.Strict
Lift a catchError operation to the new monad.
liftCatch :: (m (a, s, w) -> (e -> m (a, s, w)) -> m (a, s, w)) -> RWST l w s m a -> (e -> RWST l w s m a) -> RWST l w s m a
transformers Control.Monad.Trans.RWS.Lazy, transformers Control.Monad.Trans.RWS.Strict
Lift a catchError operation to the new monad.
liftCatch :: (m (a, w) -> (e -> m (a, w)) -> m (a, w)) -> WriterT w m a -> (e -> WriterT w m a) -> WriterT w m a
transformers Control.Monad.Trans.Writer.Lazy, transformers Control.Monad.Trans.Writer.Strict
Lift a catchError operation to the new monad.
liftCatch :: (m [a] -> (e -> m [a]) -> m [a]) -> ListT m a -> (e -> ListT m a) -> ListT m a
transformers Control.Monad.Trans.List
Lift a catchError operation to the new monad.
liftCatch :: (m a -> (e -> m a) -> m a) -> IdentityT m a -> (e -> IdentityT m a) -> IdentityT m a
transformers Control.Monad.Trans.Identity
Lift a catchError operation to the new monad.
liftCatch :: (m a -> (e -> m a) -> m a) -> ReaderT r m a -> (e -> ReaderT r m a) -> ReaderT r m a
transformers Control.Monad.Trans.Reader
Lift a catchError operation to the new monad.